Dystocia Due To Schistosomus Reflexus In A Crossbred Jersey Cow - A Case Report - Velladurai, C.; Selvaraju, M.; Napolean , R. Ezakial (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
Schistosomus reflexus is seen most commonly as anomaly of the trunk of the foetus causing dystocia. Congenital anomalies of the fetus are reported to be encountered during embryonic developmental stage in domestic animals (Ozsoy et al., 2009). Schistosomus reflexus is a major congenital fatal anomaly causing dystocia in ruminants (Suthar et al., 2011). Perusal of available literature revealed few reports on the occurrence of schistosomus reflexus in bovines in India (Jana and Ghosh, 2001). Hence, the present communication reports a case of dystocia due to schistosomus reflexus in a Jersey crossbred cow.